Assessment of the Quality of Speech Therapy Practice in Primary Health Care - Silva-Ríos, Angélica Pilar; del Campo Rivas, Manuel Nibaldo (Revista de Investigación en Logopedia, 2022)
The study of quality represents a relevant topic for users, managers and professionals of the health system. The incorporation of speech therapists into Primary Health Care (PHC) makes necessary to investigate the parameters that make up a quality practice from the perspective of service provision. The objective of this study is to validate the content of a quality matrix of speech therapy practice in PHC through expert judgment. Content validity ratio (CVR), Kendal’s (W) coefficient and content validity index (CVI) were calculated. The matrix considered three dimensions: structure, process and results. 84% of the indicators presented a positive CVR. The process and outcome dimensions presented a statistically significant Kendal coefficient (p
Keywords: Speech-Language Pathology; Quality Assurance; Health Care; Primary Health Care